Covert attention beyond the range of eye-movements: Evidence for a dissociation between exogenous and endogenous orienting. (January 2020) - Casteau, Soazig; Smith, Daniel T.
Abstract: The relationship between covert shift of attention and the oculomotor system has been the subject of numerous studies. A widely held view, known as Premotor Theory, is that covert attention depends upon activation of the oculomotor system. However, recent work has argued that Premotor Theory is only true for covert, exogenous orienting of attention and that covert endogenous orienting is largely independent of the oculomotor system. To address this issue we examined how endogenous and exogenous covert orienting of attention was affected when stimuli were presented at a location outside the range of saccadic eye movements. Results from Experiment 1 showed that exogenous covert orienting was abolished when stimuli were presented beyond the range of saccadic eye movements, but preserved when stimuli were presented within this range. In contrast, in Experiment 2 endogenous covert orienting was preserved when stimuli appeared beyond the saccadic range. Finally, Experiment 3 confirmed the observations of Exp.1 and 2. Our results demonstrate that exogenous, covert orienting is limited to the range of overt saccadic eye movements, whereas covert endogenous orienting is not. These results are consistent with a weak, exogenous-only version of Premotor Theory.